2023
DOI: 10.1007/s11356-023-25613-5
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the aerosol index and its relationship with meteorological parameters over Pakistan using remote sensing

Abstract: Particulate pollution has become a major issue in developing countries including Pakistan. Aerosols are causing severe impacts on climate and human health. To understand the effects of aerosols on the environment and human health, we must first understand their optical and physical properties. In this paper, we used ozone monitoring instrument (OMI) retrieved ultraviolet aerosol index (UVAI) to analyze spatial and temporal distribution, annual and seasonal trends of absorbing aerosols, and their relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Our finding is supported by Tariq and Ali [ 48 ], who analyzed that the increase in the flux of aerosols in the regions of Punjab and Sindh is contributed by dust and desert aerosols transported from Thar and Cholistan deserts through the wind. Also, Zhang et al [ 21 ] and Zhang et al [ 49 ] similarly pointed out high AOD values in the southern region of Pakistan (including Sindh, and Baluchistan) due to rapid increases in population, industry, and urbanization. Khan et al [ 21 ] similarly indicated the dominance of sea salt transported from the Arabian Sea over Karachi from 2004 to 2021.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our finding is supported by Tariq and Ali [ 48 ], who analyzed that the increase in the flux of aerosols in the regions of Punjab and Sindh is contributed by dust and desert aerosols transported from Thar and Cholistan deserts through the wind. Also, Zhang et al [ 21 ] and Zhang et al [ 49 ] similarly pointed out high AOD values in the southern region of Pakistan (including Sindh, and Baluchistan) due to rapid increases in population, industry, and urbanization. Khan et al [ 21 ] similarly indicated the dominance of sea salt transported from the Arabian Sea over Karachi from 2004 to 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Zhang et al [ 21 ] and Zhang et al [ 49 ] similarly pointed out high AOD values in the southern region of Pakistan (including Sindh, and Baluchistan) due to rapid increases in population, industry, and urbanization. Khan et al [ 21 ] similarly indicated the dominance of sea salt transported from the Arabian Sea over Karachi from 2004 to 2021. Ashraf et al [ 44 ] pointed out that Punjab had the highest aerosol loading which badly impacted the visibility of Punjab.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerosols are the chemical complex of solid and liquid particles suspended in air (Ahmad et al, 2020;Basharat et al, 2023;Dagestani et al, 2023;Khan et al, 2023). They can come from both natural and anthropogenic activities (Duan et al, 2021;Tariq et al, 2021.…”
Section: Introductionmentioning
confidence: 99%